Hyalinosis cutis et mucosae and Ehlers-Danlos syndrome: a rare combination of syndromes - König, Insa; Haußer-Siller, Ingrid; Anton-Lamprecht, Ingrun; Schroeter, Renate; Petzoldt, Detlef (Der Hautarzt, 1994)
We report on a 7-year-old boy suffering from two rare genetic diseases, namely hyalinosis cutis et mucosae and Ehlers-Danlos syndrome. The diagnosis was finally established after 7 years, by means of light and electron microscopy and immunohistology. Therefore, this report deals with the typical clinical and morphological features of both genetic disorders.
Gesehen am 04.10.2023